A Three-Part, Randomised Study to Investigate the Safety, Tolerability, Pharmacokinetics and Mode of Action of BC 007, Neutraliser of Pathogenic Autoantibodies Against G-Protein Coupled Receptors in Healthy, Young and Elderly Subjects - Becker, Niels-Peter; Haberland, Annekathrin; Wenzel, Katrin; Göttel, Peter; Wallukat, Gerd; Davideit, Hanna; Schulze-Rothe, Sarah; Hönicke, Anne-Sophie; Schimke, Ingolf; Bartel, Sabine; Grossmann, Matthias; Sinn, Angela; et al. (Clinical drug investigation, 2020)
Background and Objective BC 007 is a substance with a novel and innovative mode of action for the first-time causal treatment of chronic heart failure, associated with the occurrence of autoantibodies against the β1-adrenoceptor, and other diseases of mostly the heart and vascular system, being accompanied by the occurrence of functionally active agonistic autoantibodies against G-protein-coupled receptors ( f GPCR-AAb). The proposed mechanism of action of BC 007 is the neutralisation of these pathogenic autoantibodies which stimulate the respective receptor. To evaluate the safety, tolerability, pharmacokinetics and mode of action of BC 007, single intravenous infusions of increasing concentration were given to healthy young males and healthy elderly autoantibody-negative and autoantibody-positive participants of both sexes. Methods This study was subdivided into three parts. Part A was a single-centre, randomised, double-blind, placebo-controlled safety and tolerability study including healthy young male autoantibody-negative Whites ( N = 23) and Asians ( N = 1), testing doses of 15, 50 and 150 mg BC 007 (Cohorts 1–3) and elderly male and female Whites ( N = 8), testing a dose of 150 mg BC 007 (Cohort 4), randomly assigned in a 3:1 ratio to BC 007 or placebo. Open-label Part B included f GPCR-AAb-positive subjects (50 and 150 mg BC 007, Cohorts 1 and 2, respectively). Open-label Part C included f GPCR-AAb-positive subjects for testing doses of 300, 450, 750, 1350 mg and 1900 mg BC 007. Lower doses were either given as an infusion or divided into a bolus plus infusion up to a dose of 300 mg followed by a constant bolus of 150 mg up to a dose of 750 mg, while at doses of 1350 mg and 1900 mg it was a slow infusion with a constant infusion rate. Infusion times increased with increasing dose from 20 min (15, 50 or 150 mg) to 40 min (300, 450 or 750 mg), 75 min (1350 mg) and 105 min (1900 mg). Results The mean observed BC 007 area under the concentration–time curve (AUC 0–24 ) increased with increasing dose in a dose proportional manner (slope estimate of 1.039). No serious adverse events were observed. Drug-related adverse events were predominantly the expected mild-to-moderate increase in bleeding time (aPTT), beginning with a dose of 50 mg, which paralleled the infusion and returned to normal shortly after infusion. f GPCR-AAb neutralisation efficiency increased with increasing dose and was achieved for all subjects in the last cohort. Conclusion BC 007 is demonstrated to be safe and well tolerated. BC 007 neutralised f GPCR-AAb, showing a trend for a dose-response relationship in elderly healthy but f GPCR-AAb-positive subjects. ClinicalTrials.gov Registration Number NCT02955420.